Hearing impairment in murine model of Down syndrome - Chen, Guang-Di; Li, Li; McCall, Andrew; Ding, Dalian; Xing, Zhuo; Yu, Y. Eugene; Salvi, Richard (Frontiers in Genetics, 2022)
Hearing impairment is a cardinal feature of Down syndrome (DS), but its clinical manifestations have been attributed to multiple factors. Murine models could provide mechanistic insights on various causes of hearing loss in DS. To investigate mechanisms of hearing loss in DS in the absence of the cadherin 23 mutation, we backcrossed our DS mice, Dp(16)1Yey, onto normal-hearing CBA/J mice and evaluated their auditory function. Body weights of wild type (WT) and DS mice were similar at 3-months of age, but at 9-months, WT weighed 30% more than DS mice. Distortion product otoacoustic emissions (DPOAE), a test of sensory outer hair cell (OHC) function negatively impacted by conductive hearing loss, were reduced in amplitude and sensitivity across all frequencies in DS mice. The middle ear space in DS mice appeared normal with no evidence of infection. MicroCT structural imaging of DS temporal bones revealed a smaller tympanic membrane diameter, oval window, and middle ear space and localized thickening of the bony otic capsule, but no gross abnormalities of the middle ear ossicles. Histological analysis of the cochlear and vestibular sensory epithelium revealed a normal density of cochlear and vestibular hair cells; however, the cochlear basal membrane was approximately 0.6 mm shorter in DS than WT mice so that the total number of hair cells was greater in WT than DS mice. In DS mice, the early and late peaks in the auditory brainstem response (ABR), reflecting neural responses from the cochlear auditory nerve followed by subsequent neural centers in the brainstem, were reduced in amplitude and ABR thresholds were elevated to a similar degree across all frequencies, consistent with a conductive hearing impairment. The latency of the peaks in the ABR waveform were longer in DS than WT mice when compared at the same intensity; however, the latency delays disappeared when the data were compared at the same intensity above thresholds to compensate for the conductive hearing loss. Future studies using wideband tympanometry and absorbance together with detailed histological analysis of the middle ear could illuminate the nature of the conductive hearing impairment in DS mice.